Characteristics of Indigenous primary health care service delivery models: a systematic scoping review - Stephen G. Harfield; Carol Davy; Alexa McArthur; Zachary Munn; Alex Brown; Ngiare Brown (BMC, 2018)
Abstract Background Indigenous populations have poorer health outcomes compared to their non-Indigenous counterparts. The evolution of Indigenous primary health care services arose from mainstream health services being unable to adequately meet the needs of Indigenous communities and Indigenous peoples often being excluded and marginalised from mainstream health services. Part of the solution has been to establish Indigenous specific primary health care services, for and managed by Indigenous peoples. There are a number of reasons why Indigenous primary health care services are more likely than mainstream services to improve the health of Indigenous communities. Their success is partly due to the fact that they often provide comprehensive programs that incorporate treatment and management, prevention and health promotion, as well as addressing the social determinants of health. However, there are gaps in the evidence base including the characteristics that contribute to the success of Indigenous primary health care services in providing comprehensive primary health care. This systematic scoping review aims to identify the characteristics of Indigenous primary health care service delivery models. Method This systematic scoping review was led by an Aboriginal researcher, using the Joanna Briggs Institute Scoping Review Methodology. All published peer-reviewed and grey literature indexed in PubMed, EBSCO CINAHL, Embase, Informit, Mednar, and Trove databases from September 1978 to May 2015 were reviewed for inclusion. Studies were included if they describe the characteristics of service delivery models implemented within an Indigenous primary health care service. Sixty-two studies met the inclusion criteria. Data were extracted and then thematically analysed to identify the characteristics of Indigenous PHC service delivery models. Results Culture was the most prominent characteristic underpinning all of the other seven characteristics which were identified - accessible health services, community participation, continuous quality improvement, culturally appropriate and skilled workforce, flexible approach to care, holistic health care, and self-determination and empowerment. Conclusion While the eight characteristics were clearly distinguishable within the review, the interdependence between each characteristic was also evident. These findings were used to develop a new Indigenous PHC Service Delivery Model, which clearly demonstrates some of the unique characteristics of Indigenous specific models.